PENGARUH PERMAINAN SMART SNAKE-LADDER TERHADAP PERILAKU MORAL PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI KANAGARIAN SARIAK LAWEH KECAMATAN AKABILURU KABUPATEN 50 SUMATERA BARAT - Afrila, Fitri; Chairilsyah, Daviq; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aim to know the influence of game a smart snake-ladderto moral behavior of 5-6 yeard old children at TK Pertiwi Kenagarian Sariak LawehSubdistrict Akabiluru District 50 West Sumatra. Population of this reseacrh was at TKPertiwi Kenagarian Sariak Laweh Subdistrict Akabiluru District 50 West Sumatrachild’s, sample of researchare 12 childs. Method of research was experiment which thisresearch tries to look for this research aim to know the influence of the game a smartsnake-ladder to moral behavior of 5-6 yeard old children at TK Pertiwi KenagarianSariak Laweh Subdistrict Akabiluru District 50 West Sumatra. Instrumental of thisresearch used observation sheet. Data anlisa tech used utilizes scale uji-t and statisticalmethods analysis with SPSS For's program ver's Windows 23. The result of thisresearch that acquired available the influence of the a game a smart snake-ladder tomoral behavior of 5-6 yeard old children at TK Pertiwi Kenagarian Sariak LawehSubdistrict Akabiluru District 50 West Sumatra. Obtain value t count of 9,388 withsignificance 0.000. T table values obtained with df 11 at significance level of 5% (twotailed)of 2,201. Thus known t count (9.388)> t table (2,201) or significance (0.000)<5% (0.05). It has been suggested that there is a difference in the results between thepretest and posttest significant. It is known that the result of higher than pretest posttestwhich can be seen from the descriptive statistical variableIt can be seen from the valueof the interpretation of the P value of 22.18%, so it can be considered that theapplication of the influence of game a smart snake-ladder against the moral behavior ofchildren at TK Pertiwi Kanagarian Sariak Laweh Subdistrict Akabiluru District 50West Sumatra is located in the low category.Key Words: Moral Behavior, smart snake-ladder